PENERAPAN STRATEGI PEMBELAJARAN AKTIF FORMASI REGU TEMBAK (FIRING LINE) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN REAKSI OKSIDASI REDUKSI DI KELAS X SMA NEGERI 7 PEKANBARU - Fajriyati '; Rasmiwetti '; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The aim of the research was application of active learning the firing line strategy has been done to know the increasing of student’s learning achievement on oxidation reduction reaction topic in class X in 7 Senior High School Pekanbaru. This research was experiment by design pretest and posttest. The sample determined randomly after doing normality and homogeneity test of 7 classes as population and then class X5 choosed as experiment class and X2 as class group. The experiment group was applied by the application of active learning the firing line strategy. The data analysis technique used was t - test. Based on the data was obtained tcount>ttable was 2,28t ≥ 1,67, meant that the application of active learning the firing line strategy could increase the student’s learning achievement on oxidation reduction reaction topic in class X in 7 Senior High School Pekanbaru. The Category of increasing the student’s learning achievement trhough active learning the firing line strategy on the subject of oxidation reduction reaction is a high category with the N-Gain value was of 0,79.Keywords: The Firing Line, Active Learning, Achievement, oxidation reduction reaction.